What Drives Home Bias? : Evidence from Fund Managers' Views - Torben Lütje; Lukas Menkhoff (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2004)
A survey of fund managers reveals home bias for these sophisticated investors in an unrestricted setting. Proximity, perceived informational advantage and higher expected returns are confirmed as accompanying factors. In addition, the home bias of equity managers is also related to institutional, informational and behavioral characteristics. The perceived informational advantage does not seem to be valid. Multivariate analyses indicate that home bias is mainly related to relative return optimism, non-fundamental information and peculiar behavior towards risk. We interpret these as characteristics of less than fully rational behavior. It is consistently found that this pattern does not apply to bond managers. – – Eine Befragung von Fondsmanagern offenbart die Heimatverzerrung (sog. Home Bias) dieser erfahrenen Investoren in unbegrenzten Rahmenbedingungen. Nähe, empfundene Informationsvorteile und höhere erwartete Renditen werden als Begleitumstände bestätigt. Zusätzlich ist der Home Bias von Aktienfondsmanagern mit institutionellen und informatorischen Gegebenheiten sowie mit bestimmten Verhaltensmustern verbunden. Der empfundene Informationsvorteil scheint sich jedoch nicht zu bewahrheiten. Multivariate Analysen zeigen, dass der Home Bias hauptsächlich mit relativem Renditeoptimismus, der Nutzung nicht-fundamentaler Informationen und besonderem Risikoverhalten verbunden ist. Wir interpretieren diese Eigenschaften als unvollkommen rationales Verhalten. Konsistent zeigt sich, dass dieses Muster nicht für Rentenfondsmanager gilt.
Keywords: G15; G23; F30; 330; Home bias; institutional investors; local information advantage; non-fundamental information; disposition effect; Investmentfonds; Institutioneller Anleger; Anlageverhalten; Informationsverhalten; Deutschland